Documenting the 2015–2017 freshening of the eastern Eurasian Basin of the Arctic Ocean and evaluating its drivers and consequences - Dolly More; Igor V. Polyakov; Andrey V. Pnyushkov (Ocean Science, 2026)
The Arctic Ocean is undergoing rapid change, with freshwater playing a central role in shaping stratification, vertical heat exchange, and sea-ice loss. Using long-term observations from the Nansen and Amundsen Basins Observational System (NABOS), we document a strong freshening event in the eastern Eurasian Basin between late 2015 and early 2017. During this period, salinity in the upper 175 m decreased by ∼ 0.5 psu, equivalent to an additional ∼ 0.6 m of freshwater, relative to the preceding (2013–2015) and following (2017–2018) years. The anomaly originated on the Kara Sea shelves in 2014–2015, when exceptional Yenisey and Ob discharge provided a combined freshwater surplus of ∼ 0.78 m, sufficient to explain the observed freshening. Trajectory analysis traced the freshwater anomaly to the Kara Sea, with transport times of 8–9 months to the shelf and 22–23 months to offshore. The resulting enhanced stratification suppressed upper-ocean currents by ∼ 22 % and vertical shear by ∼ 50 %. These changes enabled thicker sea ice to persist through the summers of 2016–2017, in contrast to near-ice-free conditions in adjacent years. While wind anomalies aided the retention of freshwater along the slope, anomalous river discharge was the dominant driver of the event. Overall, the 2015–2017 event demonstrates how episodic river discharge events can restructure upper-ocean stratification, reduce oceanic heat fluxes, and lead to delayed melt and increased summer sea ice, highlighting the sensitivity of upper-ocean processes and sea ice to episodic freshwater forcing in the Arctic.

Role of sea ice, stratification, and near-inertial oscillations in shaping the upper Siberian Arctic Ocean currents - Igor V. Polyakov; Andrey V. Pnyushkov; Eddy C. Carmack; Matthew Charette; Kyoung-Ho Cho; Steven Dykstra; Jari Haapala; Jinyoung Jung; Lauren Kipp; Eun Jin Yang; Sergey Molodtsov (Ocean Science, 2025)
The Siberian Arctic Ocean (SAO) is the largest integrator and redistributor of Siberian freshwater resources and acts to significantly influence the Arctic climate system. Moreover, the SAO is experiencing some of the most notable climate changes in the Arctic, and advection of anomalous Atlantic- (atlantification) and Pacific-origin (pacification) inflow waters and biota continue to play a major role in reshaping the SAO in recent decades. In this study, we use a large collection of mooring data to create a coherent picture of the spatiotemporal patterns and variability of currents and shear in the upper SAO during the past decade. Although there was no noticeable trend in the upper SAO's current speed and shear from 2013 to 2023, their seasonal cycle has significantly strengthened. The cycle reveals a strong relationship between upper ocean currents and their shear with sea ice conditions – particularly during transitional seasons – evidenced by a strong negative correlation (−0.94) between seasonal sea ice concentration and current shear. In the shallow ( 100 m) layers. These findings are critical to understanding the ramifications for mixing and halocline weakening, as well as the rate of atlantification in the region.

Atmospheric Pressure Rivalry Between the Arctic and Northern Pacific: Implications for Alaskan Climate Variability - Igor V. Polyakov; Thomas J. Ballinger; James E. Overland; Stephen J. Vavrus; Seth L. Danielson; Rick Lader; Uma S. Bhatt; Amy S. Hendricks; Franz J. Mueter (International Journal of Climatology, 2024)
Located at the confluence of the Arctic and North Pacific and with Alaska at its heart, the Pacific Arctic Region (PAR) is a unique and interconnected regional climate system. Significant climatic changes in the PAR are described by a novel, mobile monthly Alaska Arctic Front (AAF) index, which is defined by sea level pressure differences between the migratory cores of the Beaufort High and Aleutian Low. Regional climate variability associated with the AAF shows prominent decadal signatures that are driven by the opposing effects of the North Pacific and the Arctic atmospheric pressure fields. Low AAF (negative phase) is dominated by North Pacific forcing, whereas high AAF (positive phase) is dominated by Arctic atmospheric processes. The recent (2011–2021) negative AAF phase, which is associated with the westward displacement of Aleutian Low explaining stronger northward winds and enhanced water transport northward through Bering Strait, is conducive to increased oceanic heat and freshwater content, reduced regional sea ice cover in the PAR, and to the expansion of Pacific species into the Arctic. These factors are all indicators of the Pacification of the Arctic Ocean, a key feature of climate change related to progression of anomalous Pacific water masses and biota into the polar basins. It is not yet clear if or when the recent phase of decadal variability will change and alter the rate of Pacification of the Arctic climate system.

Protease S of entomopathogenic bacterium Photorhabdus laumondii: expression, purification and effect on greater wax moth Galleria mellonella - Anastasia O. Svetlova; Maria A. Karaseva; Igor M. Berdyshev; Ksenia N. Chukhontseva; Olga V. Pobeguts; Maria A. Galyamina; Igor P. Smirnov; Nikita B. Polyakov; Maria G. Zavialova; Sergey V. Kostrov; Ilya V. Demidyuk (Molecular Biology Reports, 2024)

Depletion of Oxygen in the Bothnian Sea Since the Mid-1950s - Igor V. Polyakov; Kimmo Tikka; Jari Haapala; Matthew B. Alkire; Pekka Alenius; Harri Kuosa (Frontiers in Marine Science, 2022)
Glider observations conducted between 2016 and 2021 were combined with shipborne surveys from the 1950s through the 2010s to provide critically important information about changes in the Bothnian Sea. Particularly, we evaluated the rate of warming and freshening in several layers of the basin and showed that warming of 0.3°C/decade in the upper 25m was sufficient to explain ~40% of the oxygen depletion since the mid-1950s. This depletion was driven by limited saturation of the surface mixed layer (SML), caused by warming and a (related) weakening of the surface oxygen flux during spring blooms. Below the SML, the role of warming in oxygen depletion decreased to less than 30%, whereas the role of freshening became increasingly important via establishing stronger stratification that reduced local ventilation across the basin’s halocline. The observed values in this study are not critical for the ecological system of the Bothnian Sea. However, the presented trends towards oxygen depletion should be considered as an early warning sign as future projections of the oxygen levels in the Bothnian Sea suggest further severe losses of the dissolved oxygen in the next decades. Thus, enhancement of both observational networks and the current physical and biogeochemical models is a high priority if we are to mitigate the potential impact of oxygen loss and develop a reliable monitoring system of the Bothnian Sea.

Corrigendum: Borealization of the Arctic Ocean in Response to Anomalous Advection From Sub-Arctic Seas - Igor V. Polyakov; Matthew B. Alkire; Bodil A. Bluhm; Kristina A. Brown; Eddy C. Carmack; Melissa Chierici; Seth L. Danielson; Ingrid Ellingsen; Elizaveta A. Ershova; Katarina Gårdfeldt; Randi B. Ingvaldsen; Andrey V. Pnyushkov; et al. (Frontiers in Marine Science, 2021)

The Pan-Arctic Continental Slope: Sharp Gradients of Physical Processes Affect Pelagic and Benthic Ecosystems - Bodil A. Bluhm; Markus A. Janout; Seth L. Danielson; Ingrid Ellingsen; Maria Gavrilo; Jacqueline M. Grebmeier; Russell R. Hopcroft; Katrin B. Iken; Randi B. Ingvaldsen; Lis L. Jørgensen; Ksenia N. Kosobokova; Ron Kwok; et al. (Frontiers in Marine Science, 2020)
Continental slopes – steep regions between the shelf break and abyssal ocean – play key roles in the climatology and ecology of the Arctic Ocean. Here, through review and synthesis, we find that the narrow slope regions contribute to ecosystem functioning disproportionately to the size of the habitat area (∼6% of total Arctic Ocean area). Driven by inflows of sub-Arctic waters and steered by topography, boundary currents transport boreal properties and particle loads from the Atlantic and Pacific Oceans along-slope, thus creating both along and cross-slope connectivity gradients in water mass properties and biomass. Drainage of dense, saline shelf water and material within these, and contributions of river and meltwater also shape the characteristics of the slope domain. These and other properties led us to distinguish upper and lower slope domains; the upper slope (shelf break to ∼800 m) is characterized by stronger currents, warmer sub-surface temperatures, and higher biomass across several trophic levels (especially near inflow areas). In contrast, the lower slope has slower-moving currents, is cooler, and exhibits lower vertical carbon flux and biomass. Distinct zonation of zooplankton, benthic and fish communities result from these differences. Slopes display varying levels of system connectivity: (1) along-slope through property and material transport in boundary currents, (2) cross-slope through upwelling of warm and nutrient rich water and down-welling of dense water and organic rich matter, and (3) vertically through shear and mixing. Slope dynamics also generate separating functions through (1) along-slope and across-slope fronts concentrating biological activity, and (2) vertical gradients in the water column and at the seafloor that maintain distinct physical structure and community turnover. At the upper slope, climatic change is manifested in sea-ice retreat, increased heat and mass transport by sub-Arctic inflows, surface warming, and altered vertical stratification, while the lower slope has yet to display evidence of change. Model projections suggest that ongoing physical changes will enhance primary production at the upper slope, with suspected enhancing effects for consumers. We recommend Pan-Arctic monitoring efforts of slopes given that many signals of climate change appear there first and are then transmitted along the slope domain.

Oceanic Routing of Wind-Sourced Energy Along the Arctic Continental Shelves - Seth L. Danielson; Tyler D. Hennon; Katherine S. Hedstrom; Andrey V. Pnyushkov; Igor V. Polyakov; Eddy Carmack; Kirill Filchuk; Markus Janout; Mikhail Makhotin; William J. Williams; Laurie Padman (Frontiers in Marine Science, 2020)

Borealization of the Arctic Ocean in Response to Anomalous Advection From Sub-Arctic Seas - Igor V. Polyakov; Matthew B. Alkire; Bodil A. Bluhm; Kristina A. Brown; Eddy C. Carmack; Melissa Chierici; Seth L. Danielson; Ingrid Ellingsen; Elizaveta A. Ershova; Katarina Gårdfeldt; Randi B. Ingvaldsen; Andrey V. Pnyushkov; et al. (Frontiers in Marine Science, 2020)
An important yet still not well documented aspect of recent changes in the Arctic Ocean is associated with the advection of anomalous sub-Arctic Atlantic- and Pacific-origin waters and biota into the polar basins, a process which we refer to as borealization. Using a 37-year archive of observations (1981–2017) we demonstrate dramatically contrasting regional responses to atlantification (that part of borealization related to progression of anomalies from the Atlantic sector of sub-Arctic seas into the Arctic Ocean) and pacification (the counterpart of atlantification associated with influx of anomalous Pacific waters). Particularly, we show strong salinification of the upper Eurasian Basin since 2000, with attendant reductions in stratification, and potentially altered nutrient fluxes and primary production. These changes are closely related to upstream conditions. In contrast, pacification is strongly manifested in the Amerasian Basin by the anomalous influx of Pacific waters, creating conditions favorable for increased heat and freshwater content in the Beaufort Gyre halocline and expansion of Pacific species into the Arctic interior. Here, changes in the upper (overlying) layers are driven by local Arctic atmospheric processes resulting in stronger wind/ice/ocean coupling, increased convergence within the Beaufort Gyre, a thickening of the fresh surface layer, and a deepening of the nutricline and deep chlorophyll maximum. Thus, a divergent (Eurasian Basin) gyre responds altogether differently than does a convergent (Amerasian Basin) gyre to climate forcing. Available geochemical data indicate a general decrease in nutrient concentrations Arctic-wide, except in the northern portions of the Makarov and Amundsen Basins and northern Chukchi Sea and Canada Basin. Thus, changes in the circulation pathways of specific water masses, as well as the utilization of nutrients in upstream regions, may control the availability of nutrients in the Arctic Ocean. Model-based evaluation of the trajectory of the Arctic climate system into the future suggests that Arctic borealization will continue under scenarios of global warming. Results from this synthesis further our understanding of the Arctic Ocean’s complex and sometimes non-intuitive Arctic response to climate forcing by identifying new feedbacks in the atmosphere-ice-ocean system in which borealization plays a key role.

Heat, salt, and volume transports in the eastern Eurasian Basin of the Arctic Ocean from 2 years of mooring observations - Andrey V. Pnyushkov; Igor V. Polyakov; Robert Rember; Vladimir V. Ivanov; Matthew B. Alkire; Igor M. Ashik; Till M. Baumann; Genrikh V. Alekseev; Arild Sundfjord (Ocean Science, 2018)
This study discusses along-slope volume, heat, and salt transports derived from observations collected in 2013–2015 using a cross-slope array of six moorings ranging from 250 to 3900 m in the eastern Eurasian Basin (EB) of the Arctic Ocean. These observations demonstrate that in the upper 780 m layer, the along-slope boundary current advected, on average, 5.1±0.1 Sv of water, predominantly in the eastward (shallow-to-right) direction. Monthly net volume transports across the Laptev Sea slope vary widely, from ∼0.3±0.8 in April 2014 to ∼9.9±0.8 Sv in June 2014; 3.1±0.1 Sv (or 60 %) of the net transport was associated with warm and salty intermediate-depth Atlantic Water (AW). Calculated heat transport for 2013–2015 (relative to −1.8 ∘C) was 46.0±1.7 TW, and net salt transport (relative to zero salinity) was 172±6 Mkg s−1. Estimates for AW heat and salt transports were 32.7±1.3 TW (71 % of net heat transport) and 112±4 Mkg s−1 (65 % of net salt transport). The variability of currents explains ∼90 % of the variability in the heat and salt transports. The remaining ∼10 % is controlled by temperature and salinity anomalies together with the temporal variability of the AW layer thickness. The annual mean volume transports decreased by 25 % from 5.8±0.2 Sv in 2013–2014 to 4.4±0.2 Sv in 2014–2015, suggesting that changes in the transports at interannual and longer timescales in the eastern EB may be significant.

Structure and dynamics of mesoscale eddies over the Laptev Sea continental slope in the Arctic Ocean - Andrey Pnyushkov; Igor V. Polyakov; Laurie Padman; An T. Nguyen (Ocean Science, 2018)
Heat fluxes steered by mesoscale eddies may be a significant, but still not quantified, source of heat to the surface mixed layer and sea ice cover in the Arctic Ocean, as well as a source of nutrients for enhancing seasonal productivity in the near-surface layers. Here we use 4 years (2007–2011) of velocity and hydrography records from a moored profiler over the Laptev Sea slope and 15 months (2008–2009) of acoustic Doppler current profiler data from a nearby mooring to investigate the structure and dynamics of eddies at the continental margin of the eastern Eurasian Basin. Typical eddy scales are radii of the order of 10 km, heights of 600 m, and maximum velocities of ∼0.1 m s−1. Eddies are approximately equally divided between cyclonic and anticyclonic polarizations, contrary to prior observations from the deep basins and along the Lomonosov Ridge. Eddies are present in the mooring records about 20 %–25 % of the time, taking about 1 week to pass through the mooring at an average frequency of about one eddy per month. We found that the eddies observed are formed in two distinct regions – near Fram Strait, where the western branch of Atlantic Water (AW) enters the Arctic Ocean, and near Severnaya Zemlya, where the Fram Strait and Barents Sea branches of the AW inflow merge. These eddies, embedded in the Arctic Circumpolar Boundary Current, carry anomalous water properties along the eastern Arctic continental slope. The enhanced diapycnal mixing that we found within EB eddies suggests a potentially important role for eddies in the vertical redistribution of heat in the Arctic Ocean interior.

Vertical structure of recent arctic warming from observed data and reanalysis products - Vladimir A. Alexeev; Igor Esau; Igor V. Polyakov; Sarah J. Byam; Svetlana Sorokina (Climatic Change, 2012)

North Atlantic warming: patterns of long-term trend and multidecadal variability - Igor V. Polyakov; Vladimir A. Alexeev; Uma S. Bhatt; Evgenia I. Polyakova; Xiangdong Zhang (Climate Dynamics, 2010)

North Atlantic warming: patterns of long-term trend and multidecadal variability - Igor V. Polyakov; Vladimir A. Alexeev; Uma S. Bhatt; Evgenia I. Polyakova; Xiangdong Zhang (Climate Dynamics, 2010)